Novel 3-Hydroxy-2-Naphthoate-Based Task-Specific Ionic Liquids for an Efficient Extraction of Heavy Metals - Pirkwieser, Philip; López-López, José A.; Kandioller, Wolfgang; Keppler, Bernhard K.; Moreno, Carlos; Jirsa, Franz (Frontiers in Chemistry, 2018)
Ionic liquids (ILs) are per definition salts with melting points below 100°C and might be green alternatives for the extraction of heavy metals from aqueous solutions due to their favorable environmental and physico-chemical properties. Partial solution during extraction, so-called leaching, however, limits their applicability. The present study synthesizes three novel ammonium and phosphonium ILs based on 3-hydroxy-2-naphthoic acid – trihexyltetradecylphosphonium- ([P66614]), methyltrioctylphosphonium- ([P1888]) and methyltrioctylammonium 3-hydroxy-2-naphthoate ([N1888][HNA]) – by a deprotonation-metathesis route. The aims were to improve stability during extraction while still achieving high selectivity towards heavy metal ions, as well as to study the impact of different alkyl chains and the central atom of the cation on physico-chemical properties, extraction efficacy and leaching. Extraction capabilities for the seven heavy metals Ag, Cd, Co, Cu, Mn, Ni and Pb were studied in pure water at pH 8.0. Further experiments were conducted in water containing 30 g L-1 NaCl to simulate a seawater matrix and/or 30 mg L-1 humic acids, as well as metal-spiked natural water samples. All three ILs showed extraction efficacies ≥90% for Cu and Pb after 24 h. Overall, extraction efficacies for Ag, Cd, Cu and Pb were highest for drinking water samples. Ag and Cd extraction was increased by up to 41% in (hyper-) saline samples using IL [P66614][HNA] compared with pure water samples. Leaching values were reduced down to 0.07% loss of the applied IL, which can be attributed to the hydrophobic character of 3 hydroxy-2-naphthoate. Our results represent a positive development towards a greener extraction of heavy metals from natural waters.